2014
DOI: 10.1002/aic.14328
|View full text |Cite
|
Sign up to set email alerts
|

Time‐series and extended Karhunen–Loève analysis of turbulent drag reduction in polymer solutions

Abstract: in Wiley Online Library (wileyonlinelibrary.com) Direct numerical simulations and statistical analysis techniques are used to study the drag-reducing effect of polymer additives on turbulent channel flow in minimal domains. Additionally, a new formulation of Karhunen-Loe`ve decomposition for viscoelastic flows is introduced, allowing the dominant features of the polymer stress fields to be characterized. In minimal channels, there are intervals of "active" and "hibernating" turbulence that display very diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 61 publications
3
29
0
Order By: Relevance
“…These sheets of polymer conformation are accompanied by cylindrical spanwise structures of rotational and extensional flow (Dubief, Terrapon & Soria 2013;Terrapon, Dubief & Soria 2014). Wang et al (2014) affirmed the importance of spanwise independent structures in polymeric turbulent flows, and hinted at a connection between the elasto-inertial turbulence and MDR. By applying proper orthogonal decomposition to time series of both velocity and polymer stress fields from simulations of MDR in minimal flow domains, they demonstrated that the dominant modes in the hibernating state also exhibit a sheet-like structure, with large polymer stretch occurring in thin, isolated layers.…”
Section: Polymeric Turbulent Flowsmentioning
confidence: 92%
See 1 more Smart Citation
“…These sheets of polymer conformation are accompanied by cylindrical spanwise structures of rotational and extensional flow (Dubief, Terrapon & Soria 2013;Terrapon, Dubief & Soria 2014). Wang et al (2014) affirmed the importance of spanwise independent structures in polymeric turbulent flows, and hinted at a connection between the elasto-inertial turbulence and MDR. By applying proper orthogonal decomposition to time series of both velocity and polymer stress fields from simulations of MDR in minimal flow domains, they demonstrated that the dominant modes in the hibernating state also exhibit a sheet-like structure, with large polymer stretch occurring in thin, isolated layers.…”
Section: Polymeric Turbulent Flowsmentioning
confidence: 92%
“…At long time, the region of positive stretch remains despite the decay of energy and enstrophy. The stretching is isolated in a very narrow region, and is reminiscent of flow structures observed in nonlinear simulations of inertial polymer flows Agarwal et al 2014;Wang et al 2014). The mechanism behind the flow localization can be explained by contracting the polymer conformation (2.6c) to obtain the evolution of c ii , d dt…”
Section: Finite Extensibilitymentioning
confidence: 96%
“…Outcome (iii) is critical for the understanding of polymer drag reduction and specifically MDR. Previous studies have concluded that the nature of MDR is Newtonian [23,29,30,37,38] for the same marginally critical Reynolds number. However, the present results suggest that their conclusion is biased by the use of numerical methods that dissipate the small-scale dynamics critical to EIT.…”
Section: Discussionmentioning
confidence: 99%
“…To further demonstrate outcome (ii), the present results can be compared to those of Wang et al [37], who used the same Reynolds number, other polymer parameters and a Schmidt number Sc = 0.5. They reported intermediate drag reduction at Wi τ = 40 and MDR at Wi τ = 100, yet with flow structures that are clearly of Newtonian nature.…”
Section: Discussionmentioning
confidence: 99%
“…The gravity-driven method [46], two counter-rotating bladed disks systems [47], and a Taylor-Couette device [48] have also been used for measuring DR. In addition, direct numerical simulations and statistical analysis techniques are used to study the drag-reducing effect of polymer additives on turbulent channel flow in minimal domains [49,50]. Furthermore, one of the big advantages of this rotating disk flow is that the mixing time of the polymer with the flow can be estimated as the turnover time of the largest eddies which is always less than the 0.2 s injection time.…”
Section: Rotating Disk Flowmentioning
confidence: 99%